Da intersubjetividade transcendental à intersubjetividade prática: uma abordagem sócio-psicológica da estética musical kantiana - Torriani, Tristan (Faculdade de Filosofia e Ciências, 2010)
It is well known that Kant’s aesthetics is framed intersubjectively because he upholds the claim of taste to universality. However, the transcendental foundation of this shared universality is a supersensible ground which is taken for granted but which cannot be brought directly into communicative experience. Kant’s reliance on the synthetic a priori structure of aesthetic judgment also removes it from the sphere of observable personal interaction. This argumentative strategy exposes it to skeptical challenge and generates inaccessible references to inner representations (be they intuitions, categories of the understanding or rational ideas). It is not sufficient, as Kant did, to propose a description of aesthetic experience that is subjectively plausible and thereby claim its intersubjective validity. It is indispensable to embody intersubjectivity in behavior and language. In practical intersubjectivity, aesthetic attitudes are dealt with in a concrete and accessible manner without relying on mentalistic assumptions as a foundation. Conceptual terms such as ‘agreeable’, ‘beauty’, ‘sublime’, ‘ugly’, ‘universality’ acquire new meaning